UNDERSTANDING THE COMMUNICATIVE APPROACH IN ENGLISH LANGUAGE TEACHING - Xomidjonova, Gavharoy (University Research Base, 2025)
The Communicative Approach to language learning, or Communicative Language Teaching (CLT), has changed the English language teaching from a focus on grammar in learning to using the language in real life communication. CLT differs from other methods and it emphasizes memorization, practice, and accuracy, that it seeks to generate a large volume of language use that is meaningful and purposeful and often interactive. In this article, I will discuss some of the principles, benefits, and challenges of the communicative approach. I will provide a brief literature review and discuss how it develops speaking skills, inspires confidence in communication, and develops the ability to use English. Although it may be difficult to apply in large classes and with non-skilled teachers, the communicative approach has significantly progressed language acquisition.